Post-traumatic brain injury olfactory dysfunction: factors influencing quality of life - Fatimah Ahmedy; Mazlina Mazlan; Mahmoud Danaee; Mohd Zulkiflee Abu Bakar (2020)
Purpose To evaluate if and how post-traumatic brain injury (TBI) olfactory dysfunction affects the quality of life (QoL).